PENERAPAN ASAS KEADILAN DAN KEPASTIAN HUKUM TERHADAP PAJAK PENGHASILAN FINAL BAGI USAHA KECIL - Sudjana (Jurnal Hukum dan Bisnis (Selisik), 2020)
With the conditions of prison that are already overcrowded and with the current CoronaPandemic, it is easy for prisoners to be infected by Covid-19 virus. Anticipation is needed sothat the rights of prisoners to live will not be disturbed, as several policies carried out by theMinistry of Law and Human Rights, one of which is to accelerate the implementation ofassimilation and integration. The policies are in order to prevent and control the Spread ofCovid-19 virus. The policy of assimilation and integration with a reduction the term that shallbe served by the prison has modify the court's decision, even though the judge at the time ofmaking his decision had considered juridical, philosophical and sociological aspects to findout the fair punishment for the defendant. Does the prison term that should be served by theprisoners will injure justice? An analysis of this phenomenon will arrive at a discussion on theimportance of preventing prisoners from experiencing overpunishment as justification forpunishment term reduction